Variation of corticospinal excitability during kinesthetic illusion induced by musculotendinous vibration - Lauzier, Lydiane; Perron, Marie-Pier; Munger, Laurence; Bouchard, Émilie; Abboud, Jacques; Nougarou, François; Beaulieu, Louis-David (Journal of neurophysiology, 2023)
Despite being studied for more than 50 years, the neurophysiological mechanisms underlying vibration (VIB)-induced kinesthetic illusions are still unclear. The aim of this study was to investigate how corticospinal excitability tested by transcranial magnetic stimulation (TMS) is modulated during VIB-induced illusions. Twenty healthy adults received vibration over wrist flexor muscles (80 Hz, 1 mm, 10 s). TMS was applied over the primary motor cortex representation of wrist extensors at 120% of resting motor threshold in four random conditions (10 trials/condition): baseline (without VIB), 1 s, 5 s, and 10 s after VIB onset. Means of motor-evoked potential (MEP) amplitudes and latencies were calculated. Statistical analysis found a significant effect of conditions (stimulation timings) on MEP amplitudes (P = 0.035). Paired-comparisons demonstrated lower corticospinal excitability during VIB at 1 s compared with 5 s (P = 0.025) and 10 s (P = 0.003), although none of them differed from baseline values. Results suggest a time-specific modulation of corticospinal excitability in muscles antagonistic to those vibrated, i.e., muscles involved in the perceived movement. An early decrease of excitability was observed at 1 s followed by a stabilization of values near baseline at subsequent time points. At 1 s, the illusion is not yet perceived or not strong enough to upregulate corticospinal networks coherent with the proprioceptive input. Spinal mechanisms, such as reciprocal inhibition, could also contribute to lower the corticospinal drive of nonvibrated muscles in short period before the illusion emerges. Our results suggest that neuromodulatory effects of VIB are likely time-dependent, and that future work is needed to further investigate underlying mechanisms.NEW & NOTEWORTHY The modulation of corticospinal excitability when perceiving a vibration (VIB)-induced kinesthetic illusion evolves dynamically over time. This modulation might be linked to the delayed occurrence and progressive increase in strength of the illusory perception in the first seconds after VIB start. Different spinal/cortical mechanisms could be at play during VIB, depending on the tested muscle, presence/absence of an illusion, and the specific timing at which corticospinal drive is tested pre/post VIB.Despite being studied for more than 50 years, the neurophysiological mechanisms underlying vibration (VIB)-induced kinesthetic illusions are still unclear. The aim of this study was to investigate how corticospinal excitability tested by transcranial magnetic stimulation (TMS) is modulated during VIB-induced illusions. Twenty healthy adults received vibration over wrist flexor muscles (80 Hz, 1 mm, 10 s). TMS was applied over the primary motor cortex representation of wrist extensors at 120% of resting motor threshold in four random conditions (10 trials/condition): baseline (without VIB), 1 s, 5 s, and 10 s after VIB onset. Means of motor-evoked potential (MEP) amplitudes and latencies were calculated. Statistical analysis found a significant effect of conditions (stimulation timings) on MEP amplitudes (P = 0.035). Paired-comparisons demonstrated lower corticospinal excitability during VIB at 1 s compared with 5 s (P = 0.025) and 10 s (P = 0.003), although none of them differed from baseline values. Results suggest a time-specific modulation of corticospinal excitability in muscles antagonistic to those vibrated, i.e., muscles involved in the perceived movement. An early decrease of excitability was observed at 1 s followed by a stabilization of values near baseline at subsequent time points. At 1 s, the illusion is not yet perceived or not strong enough to upregulate corticospinal networks coherent with the proprioceptive input. Spinal mechanisms, such as reciprocal inhibition, could also contribute to lower the corticospinal drive of nonvibrated muscles in short period before the illusion emerges. Our results suggest that neuromodulatory effects of VIB are likely time-dependent, and that future work is needed to further investigate underlying mechanisms.NEW & NOTEWORTHY The modulation of corticospinal excitability when perceiving a vibration (VIB)-induced kinesthetic illusion evolves dynamically over time. This modulation might be linked to the delayed occurrence and progressive increase in strength of the illusory perception in the first seconds after VIB start. Different spinal/cortical mechanisms could be at play during VIB, depending on the tested muscle, presence/absence of an illusion, and the specific timing at which corticospinal drive is tested pre/post VIB.